Comparison of gonial angle with different mandibular planes on panoramic & lateral cephalometric radiographs in class I malocclusion - Muhammad Fayyaz Nafees; Naseer Ahmad Chaudhry; Muhammad Imran Rahbar; Anum Aziz; Kashif Haroon; Saad Saud Farooqui (Journal of University Medical & Dental College, 2025)
BACKGROUND&OBJECTIVES: Lateral cephalometric and panoramic radiographs are considered the gold standard in orthodontic diagnosis. Due to superimpositions, artifacts and hindrances, it becomes problematic to calculate the gonial angle on the lateral cephalogram.Because of twofold pictures of the mandible, it is hard to perceive and measure the gonial angle with reliability, while on panoramic radiograph we can measure both right and left angle individually. This study’s rationale was to compare gonial angle with different mandibular planes on panoramic & lateral cephalometric radiographs in class I malocclusion, for native population. METHODOLOGY: A cross sectional study, on 50 participants from Fatima Memorial Hospital. Gathered data was logged and examined in SPSS 20. Quantitative variables were expressed as mean and standard deviation. Categorization of gender and age was carried out to check distractors and independent t-test was used, with p-value ≤ 0.05 as significant statistically. RESULT: The patients in this study are, on average, 18.235 ±4 years old. Out of 50 patients, 19 (38%) were male and 31 (62%) were female. The majority of patients (33 (83.5%)) were between the ages of 15 to 20 years and 17 patients (16.5%) are in between 21 to 25 years of age. Mean value of Tweed’s mandibular plane on OPG and lateral cephalogram was 127±8.2497 and 124.820±8.7077 p-value = <0.05). Gender and age showed statistically insignificant differences in all other factor. CONCLUSION: This research concluded that tweeds mandibular plane shows equal reliability on lateral cephalogram and panoramic radiograph Pakistani origin.